Histological changes associated with an artificial anterior cruciate ligament. Issue 6 (June 1995) - Barry, M; Thomas, S M; Rees, A; Shafighian, B; Mowbray, M A
Abstract : AIMS--To investigate the histopathological features of the synovial lining of the knee following implantation of an artificial cruciate ligament. METHODS--Eighty two patients underwent anterior cruciate ligament reconstruction for chronic, symptomatic instability of the knee. The cruciate ligament was reconstructed with a scaffold type prosthetic ligament. All patients underwent arthroscopy at the time of cruciate reconstruction and also as a "second look" procedure at a mean 26.5 months later, at which time synovial biopsy specimens were obtained in all cases. RESULTS--The most frequent histological finding was granulomatous synovitis in 48% (39/82) of patients. Particulate polyester debris produced a greater response than carbon fibres. In 24% (20/82), nonspecific inflammation was present and in 28% (23/82) the synovium was considered normal. When the prosthetic ligament was fully covered by soft tissue in-growth, a granulomatous reaction was present in 42% (24/57), irrespective of whether the ligament was partially or totally uncovered. Stabilisation of the joint did not prevent subsequent deterioration in the articular cartilage; other factors such as increasing patient age, interval between injury and reconstruction and altered knee kinematics after reconstruction are probably important. Granulomatous synovitis was not associated with progressive chondral changes. CONCLUSIONS--Although present in 48% of cases, granulomatous synovitis was not shown to have adverse effects on either chondral surface or the prosthetic material of the ligament. Rupture of the implant is caused by mechanical factors and granulomatous synovitis is not responsible for implant failure.